#TITLE_ALTERNATIVE# - BADRIYAH (NIM : 20112016) ; Pembimbing Dr. Kuntjoro Adji Sidarto, JAMALIATUL
This thesis deals with the issue of portfolio optimization using MarkowitzÃ‚Â’s portfolio models with constrains: (1) buy in threshold, is a constraint to circumscribe weight for each asset, (2) Cardinality is a constraint to bound assets included in a portfolio, and (3) Roundlot, is a constraint which required investors only transacting in lots. With these three constraints, the portfolio optimization problem become a nonlinear optimization problem with integer and real variables. Differential Evolution will be used to solve this optimization and a modified Differential Evolution will be used to solve portfolio optimization with integer variables so this modification can solve Mixed Integer Nonlinear Programming.